EKSPLORASI PERJUANGAN TJOET NJA’ DHIEN KE DALAM BATIK GEUMASEH DAN APLIKASINYA PADA READY TO WEAR DELUXE - Muhammad, Munaya; Suharno, Suharno; Djuniwarti, Djuniwarti (Style : Journal of Fashion Design, 2024)
The geumaseh batik motif is a narrative batik that tells the story of Tjoet Nja’ Dhien’s struggle against the dutch during the Aceh war (1880-1908). In Acehnese geumaseh means an expression of love which in this case refers to Tjoet Nja’ Dhien’s love for Aceh exspressed throught her fight against the dutch. The purpose of this creation is to enrich batik motifs and ready-to-wear deluxe designs that can be used as a medium for historical education without neglecting the function of the garment itself. Ready-to-wear deluxe is chosen as a medium of expression because this type of clothing has an exclusive and luxurious character, making it appropriate to represent the greatness of Tjoet Nja' Dhien's love for Aceh. The Geumaseh motif is constructed using the hand-drawn batik technique to suit the character of ready-to-wear deluxe, taking inspiration from the 9 phases of Tjoet Nja' Dhien's struggle. The methods used in the creative process are exploration, design, and realization. The physical results of this creation are 9 (nine) ready-to-wear deluxe looks, which will be presented at the National Indonesia Fashion Week 2024 event.